BUDGET REFOCUSING POLICY OF THE MINISTRY OF SOCIAL AFFAIRS SOCIAL PROTECTION PROGRAMS IN THE COVID-19 PANDEMIC ERA - Eprina Trihariani; Bintoro Wardiyanto; Eko Supeno (RADJA PUBLIKA, 2026)
The COVID-19 pandemic has compelled governments worldwide to implement emergency budget refocusing policies, yet the capacity to execute such policies effectively remains underexplored. This study analyzes the analytical, operational/managerial, and political capacities in Indonesia's budget refocusing policy for social protection programs during the COVID-19 pandemic. Using a qualitative descriptive approach, data were collected through in-depth interviews with 11 informants from the Ministry of Social Affairs, the Ministry of Finance, facilitators, and beneficiary households, complemented by document analysis and observation. The findings reveal that while analytical capacity enabled evidence-based targeting through socio-economic registration data, weak inter-agency coordination and unintegrated information systems hindered equitable distribution. Operational capacity was demonstrated through systematic budget review processes and resource mobilization, yet was constrained by outdated beneficiary data, regulatory inconsistencies, and lengthy disbursement procedures. Political capacity, supported by stakeholder engagement and policy legitimacy, proved essential for building public trust, though implementation faced challenges including legal framework delays and data inaccuracies. The study concludes that the effectiveness of crisis-response budgeting depends on the synergy among all three capacities, with gaps in any dimension undermining overall policy performance. These findings offer critical lessons for strengthening institutional capacity in future emergency responses.